Two-step translation method for time-dependent reliability of structures subject to both continuous deterioration and sudden events. (15th December 2020) - Guo, Hong-Yuan; Dong, You; Gu, Xiang-Lin
Highlights: Time-dependent reliability analysis approach under various scenarios is developed. Component- and system-level reliability are analyzed by the proposed approach. Continuous and sudden deterioration scenarios are combined in a unified manner. Probability density function-informed method is proposed to compute reliability. Feasibility and efficiency of the proposed method are verified using examples. Abstract: Civil infrastructure can be subjected to different deterioration scenarios (e.g., continuous deterioration and sudden events) during its service life. Time-dependent reliability analysis of a deteriorating system is of vital importance in the structural design, assessment, and management process. In this paper, a general and novel probability density function-informed framework for time-dependent reliability analysis is developed, considering different deterioration processes and system-level performance. Both continuous deterioration and sudden events are considered within the proposed framework. For the scenario with random sudden drops and/or significant differences in deterioration rates, a novel two-step translation method is proposed to assess the probability density of the performance function within the service life of a structure. In this method, translation operation is conducted twice; the first time to build a virtual and differentiable performance function, and the second, to solve the actual probability density function based on the results from the first step. Then, three illustrative examples are assessed: a simple deteriorating case, a component-level case, and a system-level case. The relevant results demonstrate the feasibility and efficiency of the proposed method.